Multi-Energy Acquisition Modeling and Control Strategy of Underwater Vehicles - Shen, Shijun; Wang, Chaofan; Qiu, Zhiqiang; Ke, Zhiwu; Gong, Dawei (Frontiers in Energy Research, 2022)
An autonomous underwater vehicle (AUV) can only carry limited energy for improved flexibility, but this brings the problem of working endurance. The acquisition of environmental energy by an underwater robot is a positive way to supplement energy and increase endurance. However, the instability and difference in power output capacity of different environmental energies will lead to low utilization of environmental energy. In this study, a multi-energy acquisition model is established to manage the AUV’s energy, which includes a heart rate sampling system, a mixed-energy circuit topology, and a maximum power output algorithm of environmental energy based on power trajectory tracking. The simulating results show that the power output control strategy can effectively improve the multi-energy acquisition and utilization efficiency of underwater vehicles, which has a positive significance and could improve endurance time.